2022
DOI: 10.1002/jso.26893
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative chemotherapy for resectable colorectal liver metastases: Analysis from the Colorectal Operative Liver Metastases International Collaborative (COLOMIC)

Abstract: Background: Chemotherapy has been increasingly combined with surgery as multimodality treatment for resectable colorectal-liver metastases (CLM). There is paucity of clinical data addressing optimal timing of chemotherapy relative to surgery. We examined outcomes of patients undergoing hepatectomy for resectable CLM.Methods: Seven hundred and eighteen patients treated with hepatectomy for CLM were analyzed from five hepatobiliary institutions between 2000 and 2018. Overall survival (OS) was measured from time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…This is usually an individualized decision—taking into consideration patient comorbidities, general state of health, and patient preferences. We recently found that receiving neoadjuvant‐only chemotherapy before liver resection was not correlated with improved survival compared to surgery alone 35 . In our unmatched populations in this study, a comparable proportion of patients in both groups received chemotherapy after initial hepatectomy, but a significantly greater proportion of patients in the repeat‐hepatectomy group received chemotherapy before initial hepatectomy.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…This is usually an individualized decision—taking into consideration patient comorbidities, general state of health, and patient preferences. We recently found that receiving neoadjuvant‐only chemotherapy before liver resection was not correlated with improved survival compared to surgery alone 35 . In our unmatched populations in this study, a comparable proportion of patients in both groups received chemotherapy after initial hepatectomy, but a significantly greater proportion of patients in the repeat‐hepatectomy group received chemotherapy before initial hepatectomy.…”
Section: Discussionmentioning
confidence: 55%
“…We recently found that receiving neoadjuvant‐only chemotherapy before liver resection was not correlated with improved survival compared to surgery alone. 35 In our unmatched populations in this study, a comparable proportion of patients in both groups received chemotherapy after initial hepatectomy, but a significantly greater proportion of patients in the repeat‐hepatectomy group received chemotherapy before initial hepatectomy. However, in our PSM analysis, neoadjuvant chemotherapy before first hepatectomy was not correlated with improved survival, suggesting the treatment effect, if any, is modest at best.…”
Section: Discussionmentioning
confidence: 69%
“…The surgical resection, however, has been extended along with a few new approaches: conversion therapy, which can shrink the tumor size and potentially convert from unresectable to resectable status; extending resection to extrahepatic disease; two-stage hepatectomy; and portal vein embolization inducing hypertrophy of the future liver remnant, respectively. Furthermore, the outcome of surgical resection of HOCRC could be improved by perioperative administration of chemotherapy [32]. However, there is a high percentage of HOCRC patients in whom complete LC could be attempted but surgery is not regarded a viable option.…”
Section: Cancer Research and Treatment (Crt)mentioning
confidence: 99%
“…This trial reported the local recurrence rates of 32% and 4% at the site of ablation or resection, respectively (p<0.001) [38]. Several previous studies compared RFA and surgical resection (Table 2), which showed generally inferior local recurrence and OS rates following RFA [27][28][29][30][31][32][33][34][35][36]. Kron et al performed a systematic review of 18 published studies and reported that among the studies, 10 and 8 showed significantly higher local recurrence rates and lower OS and DFS rates in the RFA group than in the surgical resection group, respectively [39].…”
Section: Radiofrequency Ablation For Hepatic Oligometastasismentioning
confidence: 99%